MECHANISMS FOR IMPLEMENTING STATE REGULATION OF THE LOGISTICS SERVICES MARKET - SAMOILENKO, Bohdan; USTIK, Tetiana (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The logistics sector is a vital component of the economic system, playing a crucial role in improving the efficiency of production processes, ensuring the distribution of goods and services, and strengthening the overall competitiveness of the national economy. In Ukraine, as in many other countries, the demand for logistics services is constantly growing and is driven by internal and external factors. However, the efficient functioning of the logistics services market requires clear and transparent state regulation mechanisms that ensure a balance between the interests of the state, businesses, and consumers. Given the urgent need for effective state regulation of the logistics services market in Ukraine, we propose certain aspects to address the current challenges. The existing mechanisms are characterized by features such as an imperfect regulatory framework, institutional insufficiency, lack of transparency, and weak coordination with other industries. The state regulation of the logistics market in Ukraine faces numerous challenges and problems that hinder the development of infrastructure and weaken the competitiveness of the national economy. Also, the limited financial resources of the state budget are not sufficient for sufficient investment in logistics infrastructure, leading to a lack of modern equipment and software and insufficient funding for research in this area. As a result, the efficiency of logistics processes decreases while their cost increases. Consideration of the proposed mechanisms for regulating logistics, including the introduction of a single digital portal for logistics services, the development of a national Strategy for the development of the logistics system, and the creation of a state fund for logistics support, as well as a means of ensuring their comprehensiveness and complementarity. The synergy of these measures cannot only ensure the industry’s large-scale and sustainable development but also pave the way for a more efficient and competitive logistics sector. The National Logistics Development Strategy is not just a document, but a collaborative effort that selects key advantages and long-term objectives that form the basis for implementing specific initiatives and projects. It creates a clear strategic vision for the industry’s development while coordinating the efforts of government agencies, the business community, and civil society, ensuring that all stakeholders have a voice in the industry’s future. The State Fund for Logistics Development provides the necessary financial resources to implement strategic projects envisaged by the national strategy. It helps accelerate infrastructure development, support innovation, and facilitate private investment. By comprehensively applying these mechanisms, Ukraine has the potential to transform into a modern logistics hub. This transformation will not only contribute to economic growth but also improve the population’s quality of life and strengthen the country’s international position.